2007
DOI: 10.1182/blood-2007-01-064428
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolin is a receptor that mediates antiangiogenic and antitumor activity of endostatin

Abstract: The exact molecular mechanism of how endostatin inhibits angiogenesis and tumor growth remains uncharacterized. Here, we report that endostatin specifically binds to the cell surface nucleolin with high affinity. Blockage of nucleolin by a neutralizing antibody or knockdown of nucleolin by the RNA interference results in loss of antiendothelial activities of endostatin. Importantly, a neutralizing antinucleolin antibody abrogates the antiangiogenic and antitumor activities of endostatin in vivo. Nucleolin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
208
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 212 publications
(217 citation statements)
references
References 45 publications
7
208
1
1
Order By: Relevance
“…The hypothesis that nucleolin is a receptor mediating the proapoptotic effect of ADAMTS-2 may seemed challenged by the observation that HEK 293-EBNA cells are not affected by ADAMTS-2 although they express nucleolin at their surface (not shown). Similar data have been obtained with endostatin, which induces apoptosis in endothelial cells and some transformed cells while other cell types, although expressing nucleolin, are not altered [43]. Cell-specific intracellular pathways or the requirement of specific membrane co-receptors may explain this apparent discrepancy.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The hypothesis that nucleolin is a receptor mediating the proapoptotic effect of ADAMTS-2 may seemed challenged by the observation that HEK 293-EBNA cells are not affected by ADAMTS-2 although they express nucleolin at their surface (not shown). Similar data have been obtained with endostatin, which induces apoptosis in endothelial cells and some transformed cells while other cell types, although expressing nucleolin, are not altered [43]. Cell-specific intracellular pathways or the requirement of specific membrane co-receptors may explain this apparent discrepancy.…”
Section: Discussionsupporting
confidence: 71%
“…It has also been shown that nucleolin can translocate to the plasma membrane in some specific cell types such as endothelial cells and many transformed cells [42]. When present at the cell surface, it has been shown that nucleolin can interact with Erb B receptors or serves as a receptor for L-selectin, midkine and, most interestingly, endostatin [43], a potent antiangiogenic fragment of collagen XVIII. The implication of nucleolin in the control of angiogenesis was strengthened by recent publications showing that an antibody targeting the acidic domain of nucleolin caused apoptosis of cultured endothelial cells and was anti-angiogenic in vitro and in vivo [44].…”
Section: Discussionmentioning
confidence: 99%
“…Internalization of endostatin is important for its biological functions (14,17). Consistently, Lim and colleagues (18) reported that manipulation of endostatin by addition of an MTD significantly increased endostatin uptake and improved its antitumor effects.…”
Section: Endostatin Regulates Intracellular Atp Levelsmentioning
confidence: 53%
“…It can initiate endothelial cell apoptosis through the induction of VDAC1 phosphorylation, which facilitates the mitochondrial permeability transition pore (mPTP) opening (10). Moreover, it also binds to cell surface receptors such as integrins (11), glypicans (12), laminin (13) and nucleolin (14), and thereby regulates a myriad of signaling cascades. For example, endostatin binding to integrin a5b1 results in the inhibition of the FAK-c-Raf-MEK1/2-p38-ERK1 MAPK pathway (15).…”
Section: Introductionmentioning
confidence: 99%
“…The plasma membrane fractions were isolated as described. 46 Ni-NTA beads (Promega, Madison, WI, USA) coupled with rISM were incubated with the plasma membrane fraction of HUVECs. Native beads were used as the control.…”
Section: Methodsmentioning
confidence: 99%